High performance Digital Optical Switch - Singh, Ghanshyam; Gupta, S.; Jain, P.; Bothra, S.; Janyani, V.; Yadav, R.P. (Photonics Letters of Poland, 2011)
In this work, we present a high performance Y-shaped digital optical switch (DOS) which complies with the DOS reported earlier using Titanium in-diffused or proton exchanged Lithium Niobate waveguiding structures. The optimization of switching characteristics is performed for switching voltage and device size. This structure has a total length of 5.5mm and a width of 20.6um. For the first time, the driving voltage as low as 1V has been achieved with acceptable crosstalk levels (in the range of -22dB to -28dB) for communication applications. Using a beam propagation method (BPM), we demonstrate that the switch is polarization independent and suitable for low attenuation optical window (1300nm and 1550nm) operation as well. Full text: PDF References: R. Hauffe, U. Siebel, J. Bruns, K. Peterman, "Digital Optical Circuit Switches and Switching Matrices in Polymers", Int. J. Electron. Commun. 55(5), 305 (2001). [CrossRef] M. Iodice, G. Mazzi, L. Sirleto, "Thermo-optical static and dynamic analysis of a digital optical switch based on amorphous silicon waveguide", Opt. Exp. 14(12), 5266 (2006). [CrossRef] L. Sirleto, M. Iodice, F.G. Della Corte, I. Rendina, "Digital optical switch based on amorphous silicon waveguide", Opt. Lasers Eng. 45, 458 (2007). [CrossRef] P.J. Duthie, M.J. Wale, "16×16 single chip optical switch array in Lithium Niobate", Electron. Lett. 27(14), 1265 (1997). [CrossRef] H. Okkayama, M. Kawahara, ">[CrossRef] H. Okkayama, M. Kawahara, "Ti:LiNbO3 digital optical switch matrices", Electron. Lett. 29(9), 765 (1993). [CrossRef] S.J. Kim, H.S. Jung, H.Y. Lee, Jour. Opt. Soc. Korea 7(4), 253 (2003). R. Krähenbühl, M.M. Howerton, J. Dubinger, "Performance and modeling of advanced Ti:LiNbO3 digital optical switches", A.S. Greenblatt Jour. Lightwave Tech. 20(1), 92 (2002). [CrossRef] M.N. Kahn, B.I. Miller, E.C. Burrows, C.A. Burrus, "Crosstalk-, loss-, and length-reduced digital optical Y-branch switches using a double-etch waveguide structure", IEEE Photon. Technol. Lett. 11, 1250 (1999). [CrossRef] M.K. Pandit, H.P. Chan, K.S. Chiang, S. Ghosh, A.K. Das, "A digital optical switch (DOS) in polymer using truncated-structural X-branches (TSXB)", Microwave Opt. Techn. Lett. 27(4), 229 (2000). [CrossRef] R. Krähenbühl, W.K. Burns, OSA Photon. Switching 32, 160 (1999). G. Singh, R.P Yadav, V. Janyani, "Design and Analysis of Ti: LiNbO3 1x2 Digital Optical Switch with Optimized Electrode Regions", Jour. Opt. Commun. 31(2), 78 (2010). [CrossRef] Beam Prop 5.1.1, R-Soft Design Group, Inc., Physical Layer Division, 200 Executive Blvd., Ossining, NY 10562.